Cerebral aspergillosis presenting as a space occupying lesion in an immunocompetent individual - Georges El Hasbani; Joseph Chirayil; Sutasinee Nithisoontorn; Arturo Alvarez Antezana; Ibrahim El Husseini; Maria Landaeta; Yasir Saeed; Richard Assaker (Medical Mycology Case Reports, 2019)
Cerebral aspergillosis has the tendency to occur in immunocompromised patients. Less commonly, immunocompetent individuals can be affected, with neuroimaging findings being difficult to interpret. The diagnosis necessitates imaging of the brain as well as the sinuses with biopsy and pathological confirmation. A surgical excision with aggressive antifungal agents are required for a proper management. This case report describes an immunocompetent patient with cerebral aspergillosis that presented radiologically as a suspicious mass to be diagnosed pathologically and excised surgically. Keywords: Cerebral aspergillosis, Immunocompetence, Neuroimaging